Preventing postoperative complications after robot-assisted transabdominal preperetoneal repair: clinical case - D. M. Sharafutdinov; R. R. Shavaleev; I. R. Kabirov; V. N. Pavlov (Креативная хирургия и онкология)
Introduction. Inguinal hernia repair is one of the most common elective surgeries today. In our clinic, the majority of inguinal hernia repairs are performed laparoscopically. The most frequent complication after transabdominal preperitoneal inguinal hernia repair is postoperative seroma.Materials and methods. A 35-year-old patient C. with a right-sided inguinal hernia sought medical care in our clinic. He underwent robot-assisted TAPP with fluorescence lymphography using indocyanine green (ICG).Results and discussion. The present paper describes the possible relationship between intraoperative damage of the lymphatic vessels within the spermatic cord induced by robot-assisted transabdominal preperitoneal inguinal hernia repair and postoperative development of inguinal seroma. 5 mg/ml of indocyanine green was injected into the testicle on the side with the hernial bulge to visualize the lymphatic vessels. In this case such procedure is safe and feasible. Due to the tight fusion of the hernia sac with two visualized lymphatic vessels, they were excised during surgery. In the early postoperative period, an ultrasound scan revealed a subclinical seroma in the inguinal region of approximately 10 ml.Conclusion. A case series of ICG fluorescence lymphography during robot-assisted TAPP should be performed further to elucidate the relationship between lymphatic vessel damage and hydrocele.